The Influence of Professors’ Characteristics on Educational Satisfaction in Online Education Environment: Differences from Matching Online/Offline Lecture Format and Students’ Preference - SangWoo, Hahm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
After the COVID-19 pandemic, the importance of new types of lectures such as online lectures in schools has become more important. This study explains the importance of the professors’ roles in online education. In online education, the professors’ characteristics such as attitude towards students, technical competence, and communication skills will have various effects on the students' educational satisfaction. In addition, there will be situational factors necessary to increase educational satisfaction such as universities offering both online and offline lectures since the students' preferences for online and offline lectures may differ. Therefore, the influence of the professors’ characteristics may be different depending on the case when the students are provided with a lecture in a preferred format or not. These relationships show which professors’ characteristics are necessary to improve the educational satisfaction in various situations. Satisfaction with online education will increase when the professors use specific characteristics appropriate to the situation. These results will have an impact on improving the success of school education in the post-COVID-19 era.